Rainfall simulation to identify the storm-scale mechanisms of gully bank retreat - (:unkn) unknown (My University, 2011)
Gully erosion is one of the main causes of soil loss in drylands. Understanding the dominant mechanisms of erosion is important to achieve effective erosion control, thus in this study our main objective was to quantify the mechanisms involved in gully bank retreat as a result of three processes, falling of entire soil aggregates, transport of soil material by splash and by water running along gully banks (runoff). during rainfall events. The study was conducted in the sloping lands of the KwaZulu-Natal province, a region that is highly affected by gully erosion. Artificial rain was applied at 60 mm h(-1) for 45 min at the vertical wall of a gully bank typical to the area. The splash material was collected by using a network of 0.045 m(2) buckets. The sediments in the running water were assessed by sampling the runoff collected from a microplot inserted within the base of the bank, and collecting the fallen aggregates after the rainfall simulation was complete. Results indicated that the overall erosion for the simulation was 721 g m(-2) h(-1). Runoff erosion proved to be the dominant mechanism and amounted to 450g m(-2) h(-1), followed by splash and fall down of aggregates (about 170 g m(-2) h(-1)). Gully bank retreat occurred at a rate of 0.55 mm h(-1) and assuming that the soil bulk density is 1.3 g cm(-3), this corresponds to a retreat of 8.8 mm y(-1). Extrapolations to the watershed level, where about 500 m(2) of gully bank are observed per hectare, would lead to an erosion rate of 4.8 t ha(-1) y(-1). These limited results based on a simulated storm show that the three main mechanisms (runoff, splash and fall down of aggregates) are responsible for the retreat of gully banks and that to mitigate gully erosion, appropriate measures are required to control all three mechanisms. Further research studies are needed to confirm and to scale up, both in time and space, as these data are obtained at one location and from a single artificial storm. (C) 201
Keywords: African Research